Critical debates in tourism (Buffalo Channel View Publications, 2012)
In this volume tourism experts collectively discuss and debate some intriguing questions that the tourism industry poses, such as the relevance of mass tourism, the dilemma of authenticity, whether small tourism is beautiful, whether volunteer tourism is benign, whether tourism contributes to climate change, as well as many others. The book brings together the expertise of 35 renowned international scholars of tourism to examine these perplexing issues. Multidisciplinary in its content, it touches upon anthropology, sociology, geography, climatology, biosciences, and planning and development aspects of tourism. The book provides a dialogue for an academic discussion which challenges research conservatism and stereotypes in tourism studies. It will encourage scholars to test the consistency of critical notions whose heuristic value is often taken for granted.
Includes index.
Keywords: Tourism -- Social aspects; Tourism -- Environmental aspects